Nivel de conocimientos financieros y conocimientos tributarios en trabajadores de la empresa comercial Denisam, Iquitos – 2023 - Grandez Ferreyra, Eder Steven (2024)
This Study entitled Level of Financial Knowledge and Tax Knowledge in Workers of the commercial company DENISAM, Iquitos - 2023, was carried out with the objective of determining the level of financial and tax knowledge that the workers of the company DENISAM, Iquitos - 2023 have, so A descriptive type of research was chosen, with a non-experimental design, where 28 company workers who voluntarily decided to participate in this research work were taken as the study population, to whom the survey technique was applied and as an instrument the questionnaire; According to the analysis of the results obtained, it was determined that the level of financial culture is medium and the level of tax culture is at a low level, the workers of the company DENISAM, Iquitos - 2023 are of medium level, it is also concluded that the level of Financial Knowledge and Tax Knowledge in workers of the DENISAM 2023 company is of medium level.